DSTATCOM for power quality improvement in a four-wire electric distribution system. (14th November 2006) - Singh, Bhim; Adya, Alka; Mittal, A.P.; Gupta, J.R.P.
This paper deals with the simulation of a Distribution Static Compensator (DSTATCOM) for power quality improvement in a four-wire electric distribution system. A three-phase Insulated Gate Bipolar Transistor (IGBT)-based Current-Controlled Voltage Source Inverter (CC-VSI) with a DC bus capacitor is used as a DSTATCOM. The DSTATCOM improves the supply power factor, eliminates harmonics, provides load balancing and improves the load terminal voltage at the Point of Common Coupling (PCC). The DC bus voltage of the DSTATCOM and three-phase voltages at PCC are used as feedback signals for PI controllers. The control algorithm of the DSTATCOM provides three-phase reference supply currents. A carrierless hysteresis current controller is employed over the reference and sensed supply currents to generate gating pulses for the IGBTs of DSTATCOM. Simulation is carried out in the MATLAB environment using Simulink and Power System (PSB) toolboxes. Results are presented and discussed, which demonstrate power quality improvement capability of DSTATCOM system.